An integrated routing and admission control mechanism for real-time multicast connections in ATM networks. - Xiaohua Jia (IEEE Transactions on communications)
This letter presents: 1) a delay analysis model, which is specially for the admission control of real-time multicast connections in ATM networks; 2) a distributed multicast routing algorithm, which generates suboptimal routing trees under real-time constraints; and 3) a connection setup method that integrates multicast routing with admission control